If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -50 = 5x Solving -50 = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -50 + -5x = 5x + -5x Combine like terms: 5x + -5x = 0 -50 + -5x = 0 Add '50' to each side of the equation. -50 + 50 + -5x = 0 + 50 Combine like terms: -50 + 50 = 0 0 + -5x = 0 + 50 -5x = 0 + 50 Combine like terms: 0 + 50 = 50 -5x = 50 Divide each side by '-5'. x = -10 Simplifying x = -10
| 6-4x+3=31 | | -63=12.5t-4.9tsquared | | 32X*X+15=214 | | 20+3n=-2(n+8)+6n | | -63=12.5t-.9tsquared | | 0.9x+0.3(x+12)= | | 0=12.5t-4.9tsquared | | 3x+-12+6=-15 | | (25*x)+(15*y)=30500 | | 45=8+x | | 2.2x^2-120x=0 | | 20+3n=-2(n-8)+6n | | 4n-9=23 | | 12x-7=3x+5 | | 3x+5=10x-6x+1 | | 3a+50=180 | | 4K-(24+180)=20 | | y(5+6)=89 | | 9.7=x+11 | | x^2-12x=33 | | 4z+9=2x-6 | | 4x+12=2x+36 | | ln(x^2-10x-10)x=11 | | 3p^2+4=88 | | 21.5-14.2= | | 2rs-6r+4s-7rs+10r-4s= | | (5-y)(2y-9)=0 | | 2(d+2)=8 | | 3(x+4)=7x+10-4x+2 | | -m^2n-mn^2=0 | | x^2-10x-10x=11 | | 3(x-4)=2(x+11) |